Development and validation of a theory of planned behavior-based weight control behavior questionnaire among postmenopausal women with osteoporosis. Issue 10 (3rd October 2019) - Hajizadeh, Hossein; Nadrian, Haidar; Farin, Nazila; Jafarabadi, Mohammad Asghari; Hezaveh, Seyed Jamal Ghaemmaghami; Kolahi, Sousan; Azar, Pouria Sefid Mooye; Brennan-Olsen, Sharon
Abstract: Our aim was to develop a framework-based weight control behavior questionnaire (Weight-CuRB) and test its psychometric properties among a non-probability sample of 240 postmenopausal women with osteoporosis. Appropriate validity, simplicity, functionality and reliability were observed for the Weight-CuRB. The explanatory model fits the data well (χ2 [139] = 245.835, p <  .001, CFI = 0.950, NFI = 0.901, IFI = 0.950, RMSEA = 0.057[(0.045–0.068]). To our knowledge, this was the first study to develop and validate a framework-based instrument aiming at cognitive needs assessment of postmenopausal women with osteoporosis. The weight-CuRB may be useful in addressing the core cognitive determinants of weight control among the patients.